The Effect Of Rewards and Punishment on Employee Performance with Organizational Commitment as an Intervening Variableat The Representative Office Of Bank Indonesia Province North Sumatra - Fanal Nainggolan; M. Isa Indrawan; Kiki Farida Ferine (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to investigate how rewards and punishments affect employee performance, with organizational commitment acting as a mediating factor, at the Bank Indonesia Representative Office located in North Sumatra Province. A quantitative method was employed, employing Structural Equation Modeling (SEM) facilitated by SmartPLS 3.0 software. Participants in this study were employees working at the Bank Indonesia Representative Office in North Sumatra Province, and information was collected through a questionnaire that has been validated for reliability and accuracy. The findings indicate that organizational commitment has a positive effect on employee performance. Furthermore, both rewards and punishments directly enhance employee performance and organizational commitment. Indirectly, rewards and punishments also influence employee performance by increasing organizational commitment, thus confirming the mediating function of organizational commitment. These results imply that implementing a fair and appropriate reward and punishment system can improve employee performance both directly and by strengthening their commitment to the organization. The findings of this study have significant implications for human resource management, particularly regarding reward and punishment strategies to optimize performance while fostering organizational commitment.